Electrical safety handbook - Cadick, John (Mc Graw Hill, 1994)
In this handbook, electrical, safety, and plant engineers learn protective strategies for the three kinds of electrical hazards - shock, arc and blast - and safety procedures for low- and high-voltage systems. The latest OSHA, NEC, NFPA, and NESC safety standards are also reviewed.